Evaluasi Strategi Pengembangan Usaha Petik Apel pada Kelompok Tani Makmur Abadi, Tulungrejo, Kota Batu - Anis Mufida (Jurnal Ilmiah Mahasiswa FEB, 2014)
Batu is a city that has big potention in tourism industry, this city is also famous as a city of producing apples, so we can say that apple has become an icon of Batu which is very well  known  by  the  public. Nature  concept  of  tourism  industry  for  example  apples  picking tourism concept in Batu is currently become a different and interesting thing for many tourists visiting Batu. Makmur Abadi farmer group is one of a farmers group in Batu that has apples picking business units. But over the  time, with the improvement of tourism industry in Batu, the changes of the internal and external environment, exclude the situation of the competition in this industry, impact in there are many competitors who set up a similar business.  The  purpose  of  this  paper  is  to  explain  the  evaluation  of  apples  picking  business development  strategies,  include  a  description  of  the  environmental  changes  that  affect  the performance of apples picking business units in Makmur Abadi farmers group, corrective steps that can be taken, the formulation of long-term goals, and short-term goals, as well as a new strategic  plan  for  the  apples  picking  business  unit  in  the  face  of  current  environment developments, both internal and external environment .  Keywords: farmers, tourism, apples picking, Batu City